A family of genes required for maintenance of cell wall integrity and for the stress response in Saccharomyces cerevisiae - Verna, James (The National Academy of Sciences of the USA, 1997)
The PKC1–MPK1 pathway in yeast functions in the maintenance of cell wall integrity and in the stress response. We have identified a family of genes that are putative regulators of this pathway. WSC1, WSC2, and WSC3 encode predicted integral membrane proteins with a conserved cysteine motif and a WSC1–green fluorescence protein fusion protein localizes to the plasma membrane. Deletion of WSC results in phenotypes similar to mutants in the PKC1–MPK1 pathway and an increase in the activity of MPK1 upon a mild heat treatment is impaired in a wscΔ mutant. Genetic analysis places the function of WSC upstream of PKC1, suggesting that they play a role in its activation. We also find a genetic interaction between WSC and the RAS–cAMP pathway. The RAS–cAMP pathway is required for cell cycle progression and for the heat shock response. Overexpression of WSC suppresses the heat shock sensitivity of a strain in which RAS is hyperactivated and the heat shock sensitivity of a wscΔ strain is rescued by deletion of RAS2. The functional characteristics and cellular localization of WSC suggest that they may mediate intracellular responses to environmental stress in yeast.